2000
DOI: 10.1002/1529-0131(200008)43:8<1779::aid-anr14>3.0.co;2-2
|View full text |Cite
|
Sign up to set email alerts
|

Noninflammatory phagocytosis of monosodium urate monohydrate crystals by mouse macrophages: Implications for the control of joint inflammation in gout

Abstract: Objective. We have hypothesized that the process of monocyte to macrophage differentiation may alter the inflammatory response of mononuclear phagocytes to the uptake of monosodium urate monohydrate (MSU) crystals.Methods. Eight mouse monocyte/macrophage cell lines were arranged in increasing order of differentiation, as judged by expression of the macrophage markers F4/80 and BM 8 and by phagocytic capacity. Secretion of tumor necrosis factor ␣ (TNF␣) in response to MSU was measured by enzyme-linked immunosor… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

2
69
0
3

Year Published

2001
2001
2009
2009

Publication Types

Select...
5
1

Relationship

1
5

Authors

Journals

citations
Cited by 105 publications
(75 citation statements)
references
References 35 publications
2
69
0
3
Order By: Relevance
“…In contrast, freshly isolated monocytes from the same donor challenged with MSU crystals secreted these proinflammatory cytokines, induced E-selectin expression, and promoted rolling and adhesion of neutrophils on HUVECs. These observations support and extend our previous observations made with a panel of mouse monocytic cell lines, which showed divergent responses to MSU crystals according to the state of differentiation (14). Our results suggest that the process of macrophage differentiation may break the cycle of inflammation triggered by urate crystals, preventing proinflammatory cytokine synthesis, endothelial cell activation, and secondary neutrophil recruitment.…”
Section: Discussionsupporting
confidence: 92%
See 1 more Smart Citation
“…In contrast, freshly isolated monocytes from the same donor challenged with MSU crystals secreted these proinflammatory cytokines, induced E-selectin expression, and promoted rolling and adhesion of neutrophils on HUVECs. These observations support and extend our previous observations made with a panel of mouse monocytic cell lines, which showed divergent responses to MSU crystals according to the state of differentiation (14). Our results suggest that the process of macrophage differentiation may break the cycle of inflammation triggered by urate crystals, preventing proinflammatory cytokine synthesis, endothelial cell activation, and secondary neutrophil recruitment.…”
Section: Discussionsupporting
confidence: 92%
“…In order to resolve these apparently disparate observations, we hypothesized that the state of differentiation of mononuclear phagocytes may determine how they respond to urate crystal uptake. Evidence in support of this idea has been demonstrated in a study of mouse monocyte/macrophage cell lines, which showed that incompletely differentiated monocytic cell lines synthesized TNF␣ and activated endothelial cells upon challenge with urate crystals, whereas well-differentiated macrophagic lines did not (14).…”
mentioning
confidence: 85%
“…Although the mechanisms related to the initiation of acute attacks of gout have been well characterized, the mechanisms involved in the termination of these attacks are poorly understood. Removal of MSU crystals by phagocytes and dissolution of the crystals by increased solubility modulated by an increase of temperature, a decrease of pH, and a decrease of sodium and urate levels have been proposed (4)(5)(6)19). However, these explanations have not been widely accepted because crystals may remain in the inflamed joints for a long time after the acute attack has subsided (4).…”
Section: Discussionmentioning
confidence: 99%
“…Removal of MSU crystals by phagocytes, dissolution of the crystals, involvement of antiinflammatory factors, and alteration of the crystal surface by coating with serum factors have been suggested (1,(4)(5)(6). However, these explanations have not been generally accepted, and the precise mechanisms that actually cause spontaneous resolution of acute gouty arthritis remain unknown.…”
mentioning
confidence: 99%
“…After 1 wash in the same solution, cells were seeded in tissue culture dishes in low-glucose Dulbecco's modified Eagle's medium supplemented with 10% FCS, 100 g/ml of streptomycin, 100 IU/ml of penicillin, and 40 ng/ml of recombinant granulocytemacrophage colony-stimulating factor (BioSource International, Camarillo, CA) (35) at 37°C for 7-9 days. Macrophages were then assessed by flow cytometry using a FACScan (Becton Dickinson Biosciences, San Jose, CA) by staining with allophycocyanin (APC)-conjugated anti-F4/80 (Caltag, Burlingame, CA), a marker preferentially expressed by mature macrophages (36). Double staining was performed using APCconjugated anti-F4/80 and phycoerythrin-conjugated anti-TLR-2 or anti-TLR-4 (eBioscience, San Diego, CA) for TLR-2 or TLR-4 expression, or APC-anti-F4/80 and MyD88 polyclonal primary antibodies (eBioscience, San Diego, CA) and fluorescein isothiocyanate-conjugated goat anti-rabbit IgG (Jackson ImmunoResearch, West Grove, PA) as secondary antibodies for MyD88 expression.…”
Section: Methodsmentioning
confidence: 99%